A pilot translation and adaptation of the Diabetes Obstacle Questionnaire (DOQ) to measure obstacles and challenges in diabetes management for people with diabetes in Indonesia - Kusumaningrum, Niken Safitri Dyan; Handayani, Fitria (Jurnal Ners, 2024)
Introduction: Identifying the issues faced by Indonesians living with diabetes is crucial to address them appropriately. However, a standardized tool cannot measure the obstacles encountered in managing illness. Therefore, there is a need for widely accepted assessment tools to investigate these problems. This article explains the findings of the pilot translation and adaptation of the Diabetes Obstacle Questionnaire (DOQ) for people with diabetes in Indonesia. Methods: The English version of the DOQ was cross-culturally adapted and translated into Bahasa, Indonesia. The completion of the questionnaire required approximately 30 min for each of the 61 respondents, all of whom were Indonesians diagnosed with diabetes. Factor analysis, product moment, and Cronbach’s alpha were used in STATA SE 13.1 for data analysis. Results: The original 78 items underwent a systematic process of translation and adaptation to align with the Indonesian context. Twenty-one items were eliminated, leaving 57 valid question items following a judgement of expert and statistical analysis. The reliability coefficient of the Indonesian version of the DOQ was acceptable, with a value of 0.96 for all items. The coefficient varied between 0.82 and 0.99 for different scales, indicating high internal consistency reliability. Conclusions: The Indonesian version of the 57-item DOQ is an acceptable instrument that can be used to identify obstacles faced by people with diabetes in Indonesia. This can facilitate researchers in investigating the problems faced by those living with diabetes in managing their condition.